Modelo de gestión por procesos para mejorar la productividad de la empresa Eduplastic del cantón Latacunga en el período 2015-2016 - Casillas Yugcha, Ximena Margoth (2016)
The objective of this investigation was to conduct a Process Management Model for the enterprice "Eduplastic" that enabling improve its productivity, same that has been affected by several problems that the company has in the administrative and productive environment. The methodology used in the development of this investigation has contributed to the deployment of very important conclusions from the situation of the company and by the results of several elements that allowed to the strengthening of the work in the company such as the developed of strategic map, the range value, characterization sheets, sheets describe the processes, flowcharts, and a display of very important indicators that allow control of the results of these processes through the use of a balanced scorecard. This management model allows the company "Eduplastic" achieving greater competitiveness and thus attracting more customers becoming a leader in the local and regional market.